ScaleLat: A chemical structure matching algorithm for mapping atomic structure of multi-phase system and high entropy alloys - Li, Nan; Liu, Haoliang; Li, Sateng; Guo, Junming; Li, Qianwu; Shi, Fangjie; Li, Yefei; Xiao, Bing (Computer physics communications, 2024)
•ScaleLat provides a fast tool to analysis characteristic chemical structures for multi-phase systems or high entropy alloys.•An atomic cluster extraction and mapping algorithm is implemented to obtain all independent and symmetry-reduced characteristic chemical structures.•A unique chemical structure matching algorithm is employed to map all extracted atomic clusters from a large supercell onto a representative small one.•ScaleLat creates the representative supercell that bridges the gap between mesoscale and atomic scale simulations. ScaleLat (Scale Lattice) is a computer program written in C for performing the atomic structure analysis of multi-phase system or high entropy alloys (HEAs). The program implements an atomic cluster cell extraction algorithm to obtain all symmetry independent characteristic atomic cluster cells for the complex atomic configurations which are usually obtained from molecular dynamics or kinetic Monte-Carlo simulations at nanoscale or mesoscopic scale. ScaleLat implements an efficient and unique chemical structure matching algorithm to match all extracted atomic clusters from a large supercell (>104 atoms) to a representative small one (∼ 103 or less), providing the possibility to directly use the highly accurate quantum mechanical methods to study the electronic, magnetic, and mechanical properties of multi-component alloys for complex microstructures. We demonstrate the capability of ScaleLat code by conducting both the atomic structure matching analysis for Fe-12.8 at.% Cr binary alloy and equiatomic CrFeCoNiCu high entropy alloy, successfully obtaining the representative supercells containing 102∼103 atoms for two systems. The reliability of the proposed chemical structure matching scheme is tested and confirmed by calculating the electronic structures of both examples using trial supercells with various sizes. Overall, ScaleLat program provides a universal platform to efficiently map all essential chemical structures of large complex atomic structures to a relatively easy-handling small supercell for quantum mechanical calculations of various user interested properties. Program Title: ScaleLat CPC Library link to program files: https://doi.org/10.17632/cv6wsxy938.1 Developer's repository link: https://github.com/NanLi-xjtu/ScaleLat.git Licensing provisions: MIT Programming language: C Nature of Problem: Very large supercells containing more than 104 atoms must be used to describe the atomic structure of multi-phase materials or high entropy alloys, and their electronic and mechanical properties are almost not possible to be investigated using quantum mechanical calculations within conventional computational hardware. Decreasing the total number of atoms in a smaller representative supercell which preserves all essential chemical structures of the original large supercell is the key to tackling the problem. Solution to the Problem: An atomic cluster cell extraction algorithm is realized to thoroughly obtain all symmetry independent characteristic chemical structures of multi-phase system or high entropy alloys. Utilizing the direct atom swapping method, the efficient chemical structure matching procedure is developed to map all extracted characteristic atomic cluster cells of benchmark structure to the small supercell by minimizing their differences in both the types and relative fractions of atomic cluster cell sets.